Co-evolution of Immune Response in Multiple Myeloma: Implications for Immune Prevention - McCachren, Samuel S.; Dhodapkar, Kavita M.; Dhodapkar, Madhav V. (Frontiers in Immunology, 2021)
Multiple myeloma (MM), a malignant neoplasm of plasma cells that reside in the bone marrow, is universally preceded by a precursor state termed monoclonal gammopathy of undetermined significance (MGUS) – many individuals with MGUS never progress to myeloma or progress over many years, so MGUS provides a unique opportunity to surveil changes in the bone marrow tumor microenvironment over the course of disease progression. It is increasingly appreciated that MGUS cells carry many of the genetic changes found in MM. Several studies have also shown that MGUS cells can be recognized by the immune system, leading to early changes in the bone marrow immune environment compared to that of healthy individuals, including alterations in both innate and adaptive immunity. Progression to clinical MM is associated with attrition of T cells with stem-memory like features and instead accumulation of T cells with more terminally differentiated features. Recent clinical studies have suggested that early application of immune modulatory drugs which are known to activate both innate and adaptive immunity can delay the progression to clinical MM. Understanding the biology of how the immune response and tumors co-evolve over time is needed to develop novel immune-based approaches to achieve durable and effective prevention of clinical malignancy.